Pendampingan Manajemen Penguatan Citra Organisasi Pada Anggota Ismau Lampung - Sunardi, Sunardi; Ubaidillah, Ubaidillah; Senang, Senang; Kholik, Moh.; Aprilianto, Andika (An Naf'ah: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the understanding and skills of ISMA’U Lampung members in strategically and sustainably managing their organizational image. A strong organizational image is essential in building public trust, expanding networks, and increasing member engagement. However, the lack of awareness among members regarding the importance of organizational branding has led to a weak public presence of ISMA’U. The activity was held at the ISMA’U Lampung Secretariat, located in the Jombang, over two days in August 2025, using lectures and interactive discussions as the primary techniques. The materials covered included the concept of organizational image, public communication strategies, and the importance of consistent visual identity. The results showed a significant increase in awareness, understanding, and the emergence of strong commitment among participants to form a media team, develop a content calendar, and enhance the organization’s identity. The participatory approach proved effective in fostering collective awareness and behavioral change within the organization. Therefore, this activity contributes to strengthening the internal capacity of community-based organizations rooted in pesantren (Islamic boarding schools).